PENERAPAN METODE COMPUTER ASSISTEND INSTRUCTION PADA MEDIA PEMBELAJARAN PENGENALAN TUMBUHAN DIKOTIL DAN MONOKOTIL BERBASIS MULTIMEDIA - Barany Fachri; Bambang Saputra Saragih (Smart Education, 2025)
Abstract: In Natural Science (IPA) lessons there are many lessons and fields in science, one of the biology sciences introduction to dicotyledonous and monocotyledonous plants, a simulation media is needed to understand it, in the teaching and learning process every student is required to understand the material presented quickly, but not all students are interested in reading and learning on their own. With the learning media introduction to dicotyledonous and monocotyledonous plants an application is formed as a supporting media for learning, because of the use of technology, the learning media uses the Adobe Animate CC 2017 application. With the Computer Assisted Instruction (CAI) method aims to minimize teacher performance, because technology in the form of computers or smartphones is used for the educational field, so students are encouraged to study individually or in groups according to the guidelines in learning, where students must study alone or in groups. The purpose of this application is to facilitate the student learning system in self-study or independent learning so as to increase individual insight and knowledge. Students can learn or do their own exercises the application for learning simulations introduction to dicotyledonous and monocotyledonous plants is implemented in the form of an android-based learning media application in the form of materials, simulations, exercises, and games with a more attractive animated display. Keywords: Android, Interactive Learning Media, dicotyledonous and monocotyledonous plants Abstrak: Dalam pelajaran Ilmu Pengetahuan Alam (IPA) terdapat banyak pelajaran maupun bidang dalam ilmu pelajaran IPA, salah satu ilmu biologi pengenalan tumbuhan dikotil dan monokotil maka diperlukan sebuah media simulasi untuk memahami hal tersebut, dalam proses belajar mengajar setiap siswa diwajibkan memahami materi yang disampaikan dengan cepat, namun tidak semua siswa tertarik untuk membaca dan belajar sendiri. Dengan media pembelajaran pengenalan tumbuhan dikotil dan monokotil terbentuk sebuah aplikasi sebagai media pendukung untuk pembelajaran , karena pemanfaatan teknologi, media pembelajaran menggunakan aplikasi adobe animate CC 2017. Dengan metode Computer Assistend Instruction (CAI) bertujuan untuk meminimalisir kinerja guru, karena teknologi berupa komputer atau smartphone dimanfaatkan untuk bidang pendidikan, sehingga siswa dianjurkan untuk belajar individu maupun berkelompok sesuai dengan panduan dalam pembelajaran, dimana siswa harus belajar sendiri maupun berkelompok. Tujuan aplikasi ini adalah memudahkan sistem pembelajaran siswa dalam belajar sendiri atau belajar mandiri sehingga mampu meningkatkan wawasan dan ilmu individu. Siswa dapat belajar maupun mengerjakan latihan sendiri penerapan untuk simulasi pembelajaran pengenalan tumbuhan dikotil dan monokotil diterapkan dalam bentuk aplikasi media pembelajaran berbasis android berupa materi, sumulasi, latihan, dan game dengan tampilan animasi lebih menarik. Kata kunci: Android, Media Pembelajaran Interaktif, tumbuhan dikotil dan monokotil